Conceptions about educational quality among teachers in the High School Educational System at the University of Guadalajara - Olaskoaga-Larrauri, Jon; Mendoza-Sepúlveda, Carlos; Marúm-Espinosa, Elia (Education Policy Analysis Archives, 2017)
This article describes the preferences of the teachers working in the No. 9 School at the High School Education System of the University of Guadalajara, with respect to the different ways of defining the quality of education. This research establishes a relationship between teachers’ adherence to the concepts of quality and their attitudes towards some central features of the Reform of High School Education (RIEMS). We use multiple linear regressions with some dummy variables and stepwise procedures. The conclusions suggest that the teacher´s adherence to certain concepts of quality favourably influences the attitudes of the teachers towards RIEMS and, therefore, facilitates the implementation of this reform.